Effect of Light Intensity on the Growth and Chlorophyll Content of Pennywort (Hydrocotyle Bonariensis Comm. Ex Lam.) - Lim, Guat Goh (2007)
Pennywort (Hydrocotyle bonariensis) is one of the most common vegetables and medicinal herbs used in Malaysia. It was believed to help in wound-healing, blood circulation, and has effects on blood pressure, tumours and depression. Most of the pennyworts used come from the wild or are imported. Lack of knowledge regarding the agronomical parameters of this plant may affect the medicinal value of the herb, cause extinction, or loss of foreign exchange in the herb trade. This study examined the effects of light intensities and fertilizers on the growth and chlorophyll content of the pennywort. A 2x3 factorial using complete randomized block design experiment with five replicates was carried out. Thirty boxes (32 cm x 42 cm x 15 cm) of pennywort were fertilized weekly under three fertilizer conditions: organic (50 gm-2), inorganic (12.5 gm-2), and control. They were grown under moderate (542.6 μmols-1m-2) and high (1089.2 μmols-1m-2) light intensities. Results showed that leaf area was the most suitable method to determine growth. The result also exhibited that chlorophyll content in H. bonariensis was maximum in the third week of growth for all treatment. For productivity, H. bonariensis gave higher productivity compared to Centella asiatica. The most significant result was that plant in moderate light intensity was better in all growth aspects and chlorophyll content (p<0.05), except density. However, due to the bigger sized leaves, this disadvantage was negligible. Results showed that rate of fertilizing at 50 gm-2 of organic fertilizer weekly or 12.5 gm-2 inorganic fertilizers weekly was adequate to maintain healthy growth. The experimental results indicate that both organically and inorganically fertilized plants were significantly higher in all growth aspects compared to the control plant (p<0.05). However, there were no significant effects of fertilizers on plant’s chlorophyll content.